Ninety-day hospital costs for anatomic lung resections. (30th August 2018) - Brunelli, Alessandro; Crockatt, Alice; Chaudhuri, Nilanjan; Kefaloyannis, Emmanuel; Milton, Richard; Papagiannopoulos, Konstantinos; Tcherveniakov, Peter; Bassi, Vinod
Abstract: OBJECTIVES: The study aimed to assess the total cost (TC) and relative cost (RC) of 90-day postoperative care at the hospital after anatomic lung resection. METHODS: Six hundred and forty lung resections (April 2014–September 2016) were performed at a single centre (547 lobectomies, 55 pneumonectomies and 38 segmentectomies). TC was calculated up to 90 days from the date of surgery and included the postoperative cost of the index hospitalization and the costs of hospital or emergency department readmissions, clinic appointments, medications and radiology post-discharge up to 90 days from the operation. RC was calculated as the difference between the TC and the postoperative cost of the index hospitalization. Bivariate comparisons were performed by using the Mann–Whitney test. Multivariable regression analysis was used to identify the factors associated with TC. RESULTS: Median TC was €12 389.5 [interquartile range (IQR) 8455–23 043] for pneumonectomy, €9192.1 (IQR 6897–17 274) for open lobectomy, €7932.5 (IQR 5806–12 697) for video-assisted thoracoscopic surgery (VATS) lobectomy and €6609.9 (IQR 5215–13 907) for VATS segmentectomy. Median RCs were €4461.4 (IQR 1240–11 828) for pneumonectomy, €3326.8 (IQR 1626–8271) for open lobectomy, €2729.3 (IQR 1348–6312) for VATS lobectomy and €2771.5 (IQR 1229–9705) for segmentectomy. RC accounted for 36% of the TC for pneumonectomy, 36% for open lobectomy, 34% for VATS lobectomy and 42% for segmentectomy. Generalized linear models showed that age ( P = 0.024), carbon monoxide lung diffusion capacity ( P = 0.030) and body mass index ( P = 0.015) were inversely associated with TC, whereas male gender ( P = 0.054) was associated with increased cost. CONCLUSIONS: Cost-saving measures should be implemented to target not just the in-hospital but also the post-discharge period, particularly in patients with risk factors associated with increased cost.